EFEKTIVITAS PEMBELAJARAN DARING PADA MATA KULIAH PENDIDIKAN AGAMA ISLAM DALAM SITUASI PANDEMI COVID-19 - Adhika Alvianto (Universitas Islam Sultan Agung, 2020)
This study aims to determine the effectiveness of online learning in the Islamic Religious Education course in the Covid-19 pandemic situation at the Faculty of Economics, University of Sarjanawiyata Tamansiswa Yogyakarta (FE-UST). This study is also to evaluate the quality of online learning that has been implemented and as a material for developing an online learning system in the new normal era. The research method used is quantitative with a survey method. The number of samples in this study was 280 students. Collecting data using a survey method with a Likert scale. Data analysis by calculating the percentage of data on each indicator then interpreted the data percentage score and analyzed descriptively on each indicator. The results showed that the effectiveness of online learning in the Islamic Religious Education course in the Covid-19 pandemic situation at FE-UST Yogyakarta reached 74% or it was in a good category. The results of this study are also expected to be a reference in the development of online learning in tertiary institutions and as study material for further research related to the effectiveness of online learning.Keywords: Effectiveness, Online Learning, Islamic Education, Covid-19